2018
DOI: 10.1103/physreve.98.060601
|View full text |Cite
|
Sign up to set email alerts
|

Current fluctuations of interacting active Brownian particles

Abstract: We derive the distribution of particle currents for a system of interacting active Brownian particles in the long time limit using large deviation theory and a weighted many body expansion. We find the distribution is non-Gaussian, except in the limit of passive particles. The non-Gaussian fluctuations can be understood from the effective potential the particles experience when conditioned on a given current. This potential suppresses fluctuations of the particles orientations and surrounding density, aligning… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 102 publications
1
52
0
Order By: Relevance
“…While this rate function Φ x (z) was found to be related to the lowest eigenvalue of the Mathieu equation via a Legendre transform, the asymptotic behaviors of Φ x (z) were not extracted. Interestingly, the same rate function Φ x (z) was also found in the current distribution of an interacting active particle system [37], within an effective mean-field description, that just renormalises the single particle velocity v 0 which now depends on the density ρ -still, the asymptotic properties of Φ x (z) were not analysed. In this paper, we show that, for z ∈ [0, 1], the rate function Φ(z) in Eq.…”
Section: Introductionmentioning
confidence: 81%
“…While this rate function Φ x (z) was found to be related to the lowest eigenvalue of the Mathieu equation via a Legendre transform, the asymptotic behaviors of Φ x (z) were not extracted. Interestingly, the same rate function Φ x (z) was also found in the current distribution of an interacting active particle system [37], within an effective mean-field description, that just renormalises the single particle velocity v 0 which now depends on the density ρ -still, the asymptotic properties of Φ x (z) were not analysed. In this paper, we show that, for z ∈ [0, 1], the rate function Φ(z) in Eq.…”
Section: Introductionmentioning
confidence: 81%
“…Active Brownian particles provide a canonical realization of how autonomous athermal noise can drive novel steady states without simply imparting an effective temperature (17). These self-propelled agents exhibit dynamical symmetry breaking and collective motion (18,19), and previous studies have shown that the escape of active particles from a metastable potential exhibits interesting behavior arising from an interplay between the driving force, persistence time statistics, and the shape of the potential (20,21). For simplicity, we take a symmetric potential, with lA = lB = 1 and β∆VA = β∆VB = 10, setting γ = 1 and kBT = 1/2.…”
Section: θ(T) =mentioning
confidence: 99%
“…The auxiliary dynamics considered previously are for exclusion processes [84][85][86][87], particle-based diffusive systems restricted to small noise regimes [88,89] and non-interacting cases in specific potentials [90][91][92]. Interestingly, recent works have also put forward explicit solutions in active systems for a mean-field dynamics [93] and for a many-body dynamics with pair-wise forces [36].…”
Section: Phase Transitions In Biased Ensemblesmentioning
confidence: 99%